2006
DOI: 10.5020/18061230.2006.p253
|View full text |Cite
|
Sign up to set email alerts
|

Atendimento ao paciente diabético utilizando o protocolo Staged Diabetes Management: relato de experiência

Abstract: Care for diabetes patients using the Staged Diabetes Management protocol: an experience report RESUMOO trabalho em equipe multiprofissional de saúde tem sido reconhecido como importante para a educação do paciente diabético. Este estudo objetivou descrever a implementação de um programa de atendimento utilizando-se o protocolo Staged Diabetes Management e caracterizar as atividades desenvolvidas pela equipe multiprofissional de saúde do Centro Educativo de Enfermagem para Adultos e Idosos, de Ribeirão Preto, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
0
7
0
17
Order By: Relevance
“…The main difficulties regarding adherence to medication therapy are related to the number of medications used by diabetic patients, who usually present comorbidities; to the medications' adverse affects and high cost; to myths and beliefs; to the patients' instruction level, which can limit access to information and comprehension; to the disease's asymptomatic character, which most of the time makes patients not acknowledge the importance of the medication treatment (8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difficulties regarding adherence to medication therapy are related to the number of medications used by diabetic patients, who usually present comorbidities; to the medications' adverse affects and high cost; to myths and beliefs; to the patients' instruction level, which can limit access to information and comprehension; to the disease's asymptomatic character, which most of the time makes patients not acknowledge the importance of the medication treatment (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Other factors influence the individual, leading to the adoption, oftentimes, of inappropriate behavioral patterns, such as aversion to certain foods, beliefs related to supposed dangerous actions and taboos or prohibition to use or consume certain products (8) .…”
Section: Introductionmentioning
confidence: 99%
“…12 Esse tipo de comportamento alimentar está relacionado tanto a aspectos técnicos e objetivos (o que, quanto e onde se come), como também a aspectos socioculturais e psicológicos. 13 É consenso que o controle adequado do diabetes não pode ser atingido sem um planejamento alimentar. 14 A dieta para o indivíduo com diabetes mellitus objetiva contribuir para a normalização da glicemia, atingir e Os dados gerais sobre diabetes apresentam-se dispostos na tabela 5.…”
Section: Resultsunclassified
“…Relating the essential nursing intervention teaching: prescribed diet with the results reported earlier, the study revealed that the objective of nutritional care for people with diabetes is to evaluate the nutritional state and define needs, establishing attainable goals in the diet plan and metabolic control and also adjust eating based on the response and metabolic control of the individual with diabetes (19) .…”
Section: Discussionmentioning
confidence: 99%
“…A study developed in an educational center in the interior of São Paulo, Brazil to verify the implementation of a program to care for individuals with diabetes used the Staged Diabetes Management (SDM) protocol and to characterize the activities developed by the multi-professional health team verified that the use of the protocol contributed to improve the metabolic control of people with diabetes, which consequently improved medication coverage for diabetes mellitus, hypertension, and knowledge concerning the disease and also reduced the signs and symptoms reported by people with DM (19) .…”
Section: Discussionmentioning
confidence: 99%